Republic of Serbia : Financial Sector Assessment Program Update; Technical Note on Banking Sector Soundness and Stress Testing. (IMF Staff Country Reports; Country Report ;, 2010)
This Technical Note reviews banking sector soundness and stress testing in Serbia. Serbia's banking sector is well capitalized and liquid, but the corporate sector's weak performance is a source of concern because of its adverse impact on nonperforming loans. Stress tests indicate that banks are quite resilient to further adverse shocks, but they remain vulnerable to credit risk. The results highlight that the banking system is most vulnerable to further exchange rate depreciation, through foreign currency induced credit risk, and a prolonged economic downturn.